Isolation and characterization of Mycoplasma gallisepticum and Mycoplasma synoviae in poultry and birds in Peninsular Malaysia - Hossein, Taiyari (2021)
Mycoplasma gallisepticum (MG) and M. synoviae (MS) continue to cause huge economic losses to poultry industries yearly. Acute and chronic respiratory disease (CRD), sinusitis, synovitis, massive loss of body weight, decreased egg production, and reduction of hatchability rate are the sequelae of avian mycoplasmosis. The emergence of mycoplasmal conjunctivitis in wild house finch populations emphasized mycoplasmas' natural aptitude in evolving adaptability to various avian hosts. This capability contributes to the emergence of new wild reservoirs, and ultimately, the circulation of pathogens in the environment. In Malaysia, apart from reports indicating high prevalence of MG infection among commercial and backyard poultry farms, a unique strain of MG has also been identified which highlights the importance of avian mycoplasmosis in Malaysia. Despite all these efforts, there is a lack of information on optimization of detection techniques (culture and PCR), fingerprinting strains isolated from different hosts, and finally, antibiotic susceptibility profile of the field isolates. Therefore, this study was carried out to isolate, molecular characterize, and determine the antimicrobial susceptibility of MG and MS isolates from poultry and non-poultry birds in Peninsular Malaysia. Before conducting sample collection, isolation optimization was conducted by comparing the efficacy of the commonly used mycoplasma media; Frey with swine serum (FMS) and modified PPLO (Chanock) in isolation of the organism. Results showed that FMS significantly increases the chance of isolation of MG and MS in comparison to Chanock medium. Therefore, FMS was used for isolation purpose. A total of 546 choanal slit swab samples were collected from different avian species and subjected to isolation and PCR. Using immunofluorescence assay (IFA), 36.3% (198/546) MG and MS isolates were detected of which 90.4% (179/198) isolates were from poultry, and 9.6% (19/198) isolates were from non-poultry birds. For non-poultry samples, 15.8% (3/19) samples had MG colonies, and 84.2% (16/19) samples had MS colonies. For poultry samples, 26.8% (48/179) samples had MG colonies, and 73.2% (131/179) samples had MS colonies. In addition, 11 samples had both MG and MS colonies. Using PCR, a higher number of MG and MS were detected. M. gallisepticum was detected in 138 poultry samples and three non-poultry samples. For MS, 61.2% (301/492) poultry samples and 40.7% (22/54) non-poultry samples were positive by PCR. Twenty-six poultry samples were positive for both MG and MS. Phylogenetic analysis of the MG local isolates showed an identical pattern in both pvpA and mgc2 genes with MG strain F. One of the MG isolates had a different pattern of mgc2 gene from reference strains. M. synoviae field isolates shared an identical pattern of vlhA gene with MS strain MS-H. Erythromycin, lincomycin, and chlortetracycline were observed to have the highest number of resistant isolates respectively. The number of positive MG and MS infections detected by either culture or PCR is suggestive of the continuous circulation of these pathogens among birds and poultry of Malaysia. The isolation and characterization of these pathogens in free-flying birds and aviary birds highlighted the possible role of these birds as natural reservoirs. The development of AMR among local isolates of MG and MS can be related to long exposure to antibiotics or unnecessary high antibiotic dosage. Therefore, routine monitoring programs of susceptibility profile of the isolates in order to achieve effective treatment dosage is highly recommended.